Plasmonic enhancement of Rhodamine dye random lasers - Ismail W.Z.W.; Vo T.P.; Goldys E.M.; Dawes J.M. (Institute of Physics Publishing, 2024)
We demonstrate improved characteristics in Rhodamine dye random lasers with the addition of gold nanoparticles. As a result of the strong plasmonic enhancement induced by gold nanoparticles, Rhodamine 640/gold random lasers have less than half the lasing threshold compared with Rhodamine 640/alumina random lasers in the weakly scattering regime for 10-3 M dye concentration. The optimum concentration of gold nanoparticles occurs at ?8 1010 cm-3, close to the transition between the weakly scattering and diffusive regimes. Rhodamine 640 has a better performance compared with Rhodamine 6G which is attributed to the greater spectral overlap of the Rhodamine 6G fluorescence spectrum with the plasmon resonance of gold, leading to an increased energy transfer and fluorescence quenching for Rhodamine 6G by gold. We also observe the contrasting trends of lasing threshold between random dye lasers incorporating dielectric and metal nanoparticles in the diffusive scattering regime. The effects of gold nanoparticles in random dye lasers are discussed in the context of the tradeoff between local field enhancement and fluorescence quenching. 2015 Astro Ltd.